Dual Inhibition of PTP1B and DPP4 by Canavalia ensiformis Bioactive Compounds: A Synergy of Nutrition and Therapeutics - Purwanti, Elly; Rachmawati, Farida; Hasan, Aso Hameed; Nuryady, Mohamad Mirza; Permana, Tutut Indria; Prihanta, Wahyu (JSMARTech, 2025)
Diabetes mellitus affects over 460 million adults worldwide and is projected to rise further, underscoring the urgency for safe, nutrition-based strategies to improve glycaemic control. Legumes have been known for dietary intervention for diabetic patients. However, studies evaluating the functional properties of Canavalia ensiformis for diabetes management are limited. This study investigated C. ensiformis beans for their nutritional profile and therapeutic potential in diabetes management. Nutritional values were analyzed by proximate and Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES), while bioactive compounds were identified by untargeted metabolite profiling using Liquid Chromatography-High Resolution Mass Spectrometry (LC-HRMS). Anti-diabetic potential of identified bioactives was evaluated through molecular docking by using AutoDock Vina against dipeptidyl peptidase-4 (DPP4) and protein tyrosine phosphatase 1B (PTP1B) as known diabetic-associated enzymes. Nutritional analysis revealed a composition rich in crude protein (26.34%) and carbohydrates (54.84%), complemented by substantial mineral content, including calcium, iron, and zinc, which collectively support metabolic and physiological functions. Phytochemical profiling identified 22 bioactive compounds, such as flavonoids (e.g., Kaempferol), phenolic derivatives (e.g., Curcumin), and amino acids (e.g., DL-Tryptophan), known for their roles in oxidative stress reduction and glucose metabolism modulation. Molecular docking studies demonstrated that Kaempferol exhibiting binding affinities of − 7.7 kcal mol⁻¹ (DPP4) and − 7.5 kcal mol⁻¹ (PTP1B), while DL-Tryptophan showed comparable interactions. These ligands occupied the catalytic pockets of both enzymes and engaged key residues, mirroring the binding patterns of native ligands, indicating competitive inhibition that may enhance insulin signalling and prolong incretin action. The dual-target inhibition of PTP1B and DPP4, coupled with the bean’s high nutritional value, positions C. ensiformis as a promising functional food for diabetes management, merging dietary benefits with therapeutic potential. Keywords: Functional food, Diabetes Mellitus, Dietary Intervention, DPP4 inhibitor, PTP1B inhibitor.